(untitled) (Web of Teachers: Inderscience Research, 2024)
Everyone who has knowledge can teach it to others. They teach according to their abilities. To choose the right teaching and learning strategies for a mathematics topic, you need to be aware of various approaches and teaching methods. We explain the distinction between teaching approaches, methods, and techniques as follows.